2016
DOI: 10.5152/iao.2015.1572
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Progressive Hearing Loss Due to Paget’s Disease of Bone - A Case Report and Literature Review

Abstract: A 73-year old man seeking treatment for bilateral severe hearing loss visited our department. When he was 47 years old, he was found to have high levels of serum alkaline phosphatase (ALP) with normal serum calcium levels. However, a needle bone biopsy and a bone scan did not yield an accurate diagnosis. Since then, his hearing became progressively worse and required hearing aids. At his first visit to our department, audiological assessment revealed a bilateral severe hearing loss and an air-bone gap with 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…[99] with isolated cases of conductive hearing loss reported for this reason [96]. Regarding calcitonin, several articles have described auditory improvement in patients with Paget's disease [97,98]. More recently, the door has been opened to use this hormone in the treatment of otosclerosis.…”
Section: Bone Metabolism and Middle Ear Pathologymentioning
confidence: 99%
“…[99] with isolated cases of conductive hearing loss reported for this reason [96]. Regarding calcitonin, several articles have described auditory improvement in patients with Paget's disease [97,98]. More recently, the door has been opened to use this hormone in the treatment of otosclerosis.…”
Section: Bone Metabolism and Middle Ear Pathologymentioning
confidence: 99%
“…Как было сказано ранее, к самому распространенному неврологическому осложнению КБП относится снижение остроты слуха вследствие вовлечения пирамид височных костей [4,6,[22][23][24]. Недавние исследования выявили нарушение метаболического гомеостаза улитки из-за выработки местных цитокинов [24], также важную роль отводят дефициту остеопротегерина, ключевого ингибитора дифференциации и активации остеокластов, что приводит к де-миелинизации и дегенерации нейронов спирального ганглия [23].…”
Section: особенность поражения слухового анализатора при костной болеunclassified
“…Недавние исследования выявили нарушение метаболического гомеостаза улитки из-за выработки местных цитокинов [24], также важную роль отводят дефициту остеопротегерина, ключевого ингибитора дифференциации и активации остеокластов, что приводит к де-миелинизации и дегенерации нейронов спирального ганглия [23]. Прежние представления о роли в патогенезе тугоухости при КБП таких изменений, как фиксация слуховых косточек и компрессия VIII пары черепного нерва вследствие стеноза внутреннего слухового прохода не подтвердились [4,6,22]. Тугоухость у пациентов с БПК не имеет характерных особенностей и может относиться к кондуктивному, смешанному и сенсоневральному типам.…”
Section: особенность поражения слухового анализатора при костной болеunclassified
See 1 more Smart Citation
“…Patients with PDB have symptoms including bone pain, fractures, neurological complications due to spinal cord compression, deafness and dental abnormalities [2]. It has been reported that approximately 1% PDB patients have an incidence of osteosarcoma [3,4]. PDB has a variable geographic distribution, with an increased incidence in Caucasians of European origin, but it also occurs in African-Americans and Asian descent.…”
Section: Introductionmentioning
confidence: 99%